Evaluating the provision of information system performance in the public education sector : An extension of DeLone and Mclean model / Mohd Aidil Riduan Awang Kader and Roslina Ali - Awang Kader, Mohd Aidil Riduan; Ali, Roslina (Universiti Teknologi MARA Cawangan Pahang, 2012)
The DeLone & McLean Information System (IS) Success model has been the definitive framework to measure IS effectiveness. This model has been used in many settings like education and business, but less frequently in the e-government environment. Therefore, this paper aims to measure the IS performance and its importance to the users particularly in public education sector by using an extension of DeLone & McLean model. Respondents comprise of a local public education sector end users (employees) who had access to Information Technology (IT) facilities and services (email, internet browsing and a host of office automation system). A total of 151 responses were obtained. The specific objective of this study includes to identify the IS attribute (amongst systems quality, information quality and service quality), which is perceived to have the most significant relationship with end-user satisfaction. Furthermore, this study seeks to examine the relationship between the demographic factors of the end-users and their evaluation of the overall IS performance. The findings indicate that system quality has the most significant relationship with enduser satisfaction. However, the study also found that there is no significant relationship between the end user demographic factors and their evaluation of the overall IS performance. Findings from this study could give public managers the basis to perform a benchmark amongst the different IS applications. In addition, the results can also be considered by top level management in developing future policies and strategies to exploit organization’s information resources, develop its information infrastructure, and promote the utilization of IS for the purpose of achieving more effective growth in the public services